Transforming Arabic Language Learning Through Kumaravadiveli's Epistemology - Masykur, Muhammmad Zakki; Agustina, Ahadiah; Dewi, Novi Yanti Sandra; Izomi, Syahrul; Wardi, M. Musfiatul; Masykur, M. Zaki; Sardi, Janudin; Nasarudin, Nasarudin (UIN ANTASARI, 2024)
This study aims to explain Kumaravadivelu's epistemology in transforming Arabic language learning through postmethod and beyond-method approaches. The research method used is a literature study, which involves analyzing Kumaravadivelu's works as well as other related research in this field. The analysis shows that with Kumaravadivelu's epistemology of postmethod (including postmethod conditions, postmethod pedagogy and postmethod praxis) and beyond method (including macrostrategies and microstrategies), Arabic language learning can be transformed to be more responsive and adaptive to students' needs and local contexts. Postmethod encourages teachers to be reflective and innovative practitioners, while the Beyond Method framework provides macrostrategy guidelines that allow for flexible and contextualized application. This transformation not only enhances the effectiveness of Arabic language teaching but also empowers students as independent, critical and free learners. This transformation marks a paradigmatic shift from a static approach to Arabic language teaching towards a more contextualized, practical and possibility-oriented approach.